Insights to Heart Development and Cardiac Disease Models Using Pluripotent Stem Cell Derived 3D Organoids - Pang, Jeremy Kah Sheng; Ho, Beatrice Xuan; Chan, Woon-Khiong; Soh, Boon-Seng (Frontiers in Cell and Developmental Biology, 2021)
Medical research in the recent years has achieved significant progress due to the increasing prominence of organoid technology. Various developed tissue organoids bridge the limitations of conventional 2D cell culture and animal models by recapitulating in vivo cellular complexity. Current 3D cardiac organoid cultures have shown their utility in modelling key developmental hallmarks of heart organogenesis, but the complexity of the organ demands a more versatile model that can look into more fundamental parameters, such as structure, organization and compartmentalisation of a functioning heart. This review will cover the prominence of cardiac organoids in recent research, unpack current in vitro 3D models of the developing heart and look into the prospect of developing physiologically appropriate cardiac organoids with translational applicability. In addition, we discuss some of the limitations of existing cardiac organoid models in modelling embryonic development of the heart and manifestation of cardiac diseases.